Bacteriocin production of the probiotic Lactobacillus acidophilus KS400 - Gaspar, C (2020)
In the last years, the use of probiotics, including Lactobacillus species, has received much attention to prevent and treat vaginal disorders. These species have been described as having the ability to colonize the epithelial surface and produce antimicrobial metabolites that are able to control the remaining vaginal microflora. This study aimed to identify and characterize, for the first time, a bacteriocin natively produced by Lactobacillus acidophilus KS400 (probiotic strain from Gynoflor®-Medinova AG, Switzerland) and its antimicrobial activity against relevant urogenital pathogens. After organic acids and hydrogen peroxide neutralization in the fermented Lactobacillus acidophilus KS400 culture medium, bacteriocin activity was tested against the indicator microorganism Lactobacillus delbrueckii ATCC9649. The fermentation of Lactobacillus acidophilus KS400 for bacteriocin production was carried out in batch mode, and its antimicrobial activity, optical density and pH were monitored. After production and extraction, the bacteriocin molecular weight was estimated by electrophoresis and tested against vaginal pathogenic microorganisms. As described for other bacteriocins, batch fermentation profiles indicated that bacteriocin production occurs during the exponential growth phase of the lactobacilli, and declines during their stationary growth phase. The molecular weight of the bacteriocin is approximately 7.5 kDa. The bacteriocin containing protein extract was shown to inhibit the growth of Gardnerella vaginalis, Streptococcus agalactiae, Pseudomonas aeruginosa and the indicator strain Lactobacillus delbrueckii ATCC9649. We conclude that L. acidophilus KS400 produces bacteriocin with antimicrobial activity against relevant urogenital pathogens.